Bentuk Penyajian dan Fungsi Musik Pada Ritual Amot Samper di Desa Menyabo Kecamatan Tayan Hulu Kabupaten Sanggau - Agustinusa, Agustinusa; Ghozali, Imam (Universitas Tanjungpura, 2022)
This research is motivated by the uniqueness of the Amot Samper ritual, which is very lively but has a very simple form of presentation. This research is focused on (1) the form of presentation of the ritual of amot Samper and (2) the function of music in the ritual of amot Samper. This study uses a descriptive method with a musicological approach. Interviews, observations, and documentation yielded data. The data validity technique uses source triangulation and observation extension. The data in this study was analyzed using the theory of Miles and Huberman. The results of this study indicate the uniqueness of the form of presentation and function of music in the Amot Samper ritual. The uniqueness of Amot's form of presentation is that the costumes are made from a collection of fibers, the masks are made of wood, and the stage used is the entire village. In the Amot Samper ritual, music has various functions, namely education, communication, entertainment, and economic functions. From the results of this study, it can be used as a reference for studying the ritual of Amot Samr in Menyabo Village, Tayan Hulu District, Sanggau Regency